High-resolution MR imaging with gadoxetate disodium for the comprehensive evaluation of potential living liver donors. Issue 5 (6th May 2023) - Lee, Yoonseong; Koh, Seok Young; Kim, Jae Hyun; Yoo, Jeongin; Kang, Hyojin; Joo, Ijin; Yoon, Jeong Hee; Yi, Nam-joon; Lee, Kwang-Woong; Suh, Kyungsuk; Lee, Jeong Min
Abstract : Several major transplantation centers have used composite multimodality evaluation for the preoperative evaluation of potential living liver donors. This approach can be time-consuming and, although rare, can cause complications. We aimed to demonstrate the clinical feasibility of our comprehensive preoperative MR protocol for the preoperative assessment of living liver donor candidates instead of composite multimodality evaluation. Thirty-five consecutive living liver donor candidates underwent multiphasic liver CT and comprehensive donor protocol MR examinations for preoperative evaluation in a single large-volume liver transplantation (LT) center. Three blinded abdominal radiologists reviewed the CT and MR images for vascular and biliary variations. The strength of agreement between CT and MR angiography was assessed using the kappa index. The detection rate of biliary anatomical variations was calculated. The sensitivity and specificity for detecting significant steatosis (>5%) were calculated. The estimated total volume and right lobe volumes measured by MR volumetry were compared with the corresponding CT volumetry measurements using the intraclass correlation coefficient (ICC). Among the 35 patients, 26 underwent LT. The measurement of agreement showed a moderate to substantial agreement between CT and MR angiography interpretations (kappa values, 0.47–0.79; p < 0.001). Combining T2-weighted and T1-weighted MR cholangiography techniques detected all biliary anatomical variations in 9 of the 26 patients. MR-proton density fat fraction showed a sensitivity of 100% (3/3) and a specificity of 91.3% (21/23) for detecting pathologically determined steatosis (>5%). MR volumetry reached an excellent agreement with CT volumetry (reviewers 1 and 2: ICC, 0.92; 95% CI, 0.84–0.96). Our one-stop comprehensive liver donor MR imaging protocol can provide complete information regarding hepatic vascular and biliary anatomies, hepatic parenchymal quality, and liver volume for living liver donor candidates and can replace composite multimodality evaluation.